INFLUENCE OF PRACTICAL LEVEL ON DECISION MAKING IN HANDBALL - Sebbane Mohammed; Benkazdali el Hadj Mohammed (European Scientific Journal, ESJ, 2015)
Various studies on cognitive expertise have developed a new approach to describing the superiority of experts on novices as a benefit of directory knowledge acquired at the heart of practice. This study had as its main objective to confirm the superiority of cognitive performance sports experts. Indeed, the interaction of conceptual knowledge (treatment level) and perceptual knowledge (low-level processing) optimizes performance through a rapid recall and recognition memory knowledge among experts. It does not reach this performance was achieved in the novices. The results confirm that a large repertoire of knowledge acquired through practice facilitates the response to the demands of sporting tasks.